Adding Four Extra K-Regions to Hexa-peri-hexabenzocoronene - Dumslaff, Tim; Yang, Bo; Maghsoumi, Ali; Velpula, Gangamallaiah; Mali, Kunal S.; Castiglioni, Chiara; De Feyter, Steven; Tommasini, Matteo; Narita, Akimitsu; Feng, Xinliang; Muellen, Klaus (Journal of the American Chemical Society, 2016)
A multistep synthesis of hexa-peri-hexabenzocoronene (HBC) with four additional K-regions was developed through a precursor based on two benzotetraphene units bridged with p-phenylene, featuring preinstalled zigzag moieties. Characterization by laser desorption/ionization time-of-flight mass spectrometry, Raman and IR spectroscopy, and scanning tunneling microscopy unambiguously validated the successful formation of this novel zigzag edge-rich HBC derivative. STM imaging of its monolayers revealed large-area, defect-free adlayers. The optical properties of the modified HBC were investigated by UV/visible absorption spectroscopy.
CRIS-Team Scopus Importer:2023-03-20